Diversity of Hymenoptera in Indonesian Rice Agroecosystems: A Systematic Review of Species Composition and Ecological Roles - Ikhsan, Zahlul (Universitas Andalas, 2024)
Hymenoptera are vital for maintaining ecological balance in rice agroecosystems. These insects provide essential ecosystem services, particularly in biological pest control, reducing the reliance on chemical pesticides. Despite their importance, the impact of different agricultural practices on Hymenoptera diversity and their ecological roles in Indonesian rice fields remains underexplored. This systematic review aims to assess the diversity and ecological functions of Hymenoptera in Indonesian rice agroecosystems, evaluate their contributions to natural pest suppression, and examine how various management practices, including organic farming and Integrated Pest Management (IPM), affect Hymenoptera populations. A comprehensive search of peer-reviewed studies from Scopus, Web of Science, and Google Scholar was conducted. Inclusion criteria focused on studies reporting Hymenoptera species diversity, ecological roles, and the effects of different rice farming practices. Data on species composition, pest suppression rates, and management practices were synthesized and analyzed using statistical methods, including regression and ANOVA.The findings reveal significant variation in Hymenoptera diversity across regions, with organic and IPM practices supporting higher species richness than conventional methods. A strong positive correlation was found between Hymenoptera diversity and pest suppression rates, particularly during the reproductive stage of rice growth. Parasitoids and predators played dominant roles in controlling key rice pests.Conserving Hymenoptera diversity through sustainable farming practices is crucial for reducing chemical inputs, improving pest control, and enhancing the resilience of rice agroecosystems. Future agricultural strategies should integrate biodiversity-friendly practices to ensure long-term sustainability in rice production.